Futures of the Study of Culture: Interdisciplinary Perspectives, Global Challenges - Bachmann-Medick, Doris; Nünning, Ansgar; Kugele, Jens (Concepts for the Study of Culture (CSC), 2020)
How can we approach possible but unknown futures of the study of culture? This volume explores this question in the context of a changing global world. The contributions in this volume discuss the necessity of significant shifts in our conceptual and epistemological frameworks. Taking into account changing institutional research settings, the authors develop pathways to future cultural research, addressing the crucial concerns of the cultural and social worlds themselves. The contributions thereby utilize contact zones within a wide range of disciplines such as cultural anthropology, sociology, cultural history, literary studies, the history of science and bioethics as well as the environmental and medical humanities. Examining emerging inter- and transdisciplinary points of reference, the volume invites scholars in the humanities and social sciences to take part in a conversation about theories, methods, and practices for the future study of culture.